SISTEM INFORMASI PELAYANAN DAN KOORDINASI KEGIATAN IBADAH BERBASIS WEB - Wang, Jensen; Tony; Wasino (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Web-Based Service Information System and Coordination of Worship Activities for the Next Gen Community at the House of Prayer Church is a web application designed to help ministers from fields involved in worship activities to coordinate with one another and for data processing of congregations, ministers, mentors to be better. The coordination process for services and worship, as well as scheduling is now still being done manually without using a digital system, namely by holding face-to-face meetings at the church or using online messaging services. Therefore, the purpose of creating this web application is so that worship activities can be better and more coordinated. Making this application uses waterfall methodology. The programming languages used are HTML, CSS, Javascript, and PHP with the Bootstrap Framework. The database used is MySQL. After going through the development process, the application is tested using black-box testing which results are satisfactory for the developer. Based on the result of user acceptance testing, the user indicator has a “very good” category.